STUDY ON THE THERMAL STABILITY OF EPA AND DHA IN MUJAHIR (Oreochromis mossambicus) FISH OIL - Ngatidjo Hadipranoto (Universitas Gadjah Mada, 2005)
EPA (Eicosapentaenoic acid) and DHA (Docosahexaenoic acid) content in common fresh water fish : mujahir (Oreochromis mossambicus) after indirect heating were analysed. The aims of this study were to determine the effect of indirect heating process and α-tocopherol additions on both fatty acid stability.Lipids content in the mujahir fillets were extracted by Folch method using chloroform-metanol (2:1) mixture. Fatty acids in fish oil were converted to fatty acid methyl esters and then injected into gas chromatography to determine the EPA and DHA concentration. Operating condition of gas chromatography were programmed as follows: injection port temperature at 270 oC, detector at 280 oC, initial column temperature at 200 oC, and the final at 280 oC, the carrier gas was helium with flow rate of 10 ml per minute and temperature of column was increased gradually at 10 oC per minute. The effect of α-tocopherol addition on the stability of EPA and DHA was studied by adding α-tocopherol at 50 to 200 mg per kilogram sample before indirect heating process was carried out.The analysis of mujahir fish oil showed that the content of EPA and DHA in 100 grams fresh sample was 105 and 406,5 mg respectivelly. Indirect heating caused the EPA and DHA content decreased significantly. The addition of α-tocopherol results in a positive corelation between α-tocopherol concentration added and the decrease of EPA and DHA content during the heating process.